A CRITICAL STUDY OF THE THERAPEUTIC EFFECT OF TRATAKA AND JALA NETI ON MYOPIA - Chauhan, Shilpesh; Pal, Biman Bihari (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Myopia is an emerging global health problem. It is a rapidly increasing eye-related problem which has become a serious concern not only in India but all over the world. The prevalence of this problem is increasing among children and youth especially in urban areas. Due to myopia, a person sees distant objects blurred which affects daily activities. Traditional treatment methods include glasses, lenses, surgery. Trataka and Jala Neti have been described effectively in Indian Yoga Shastra to maintain eye health. This paper critically discusses the effects of Trataka and Jala Neti on myopia to understand how these yogic practices can help in the management of myopia.